2016
DOI: 10.18869/acadpub.cmm.2.4.46
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum PCR assay and histopathology for the diagnosis of invasive aspergillosis and mucormycosis in immunocompromised patients with sinus involvement

Abstract: Background and Purpose:Invasive fungal infections cause morbidity and mortality in patients with hematologic malignancies and immunosuppression. Although these infections are commonly caused by Candida and Aspergillus species, infections caused by Mucoralean fungi are also on a growing trend. The definitive diagnosis of mucormycosis includes visualization of non-septate hyphae on pathology or growth of Mucoralean fungi culture. Polymerase chain reaction (PCR) is used to diagnose mucormycosis from paraffin bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…11 Although previous studies have evaluated the diagnostic usefulness of blood PCR in patients with invasive aspergillosis or mucormycosis, 4,[12][13][14] there are limited data on the differential diagnosis of invasive aspergillosis and mucormycosis by using blood fungal PCR in patients with suspected invasive mould infections. 15,16 In In our study, blood PCR invasive aspergillosis showed lower sensitivity and higher specificity than in previous studies. TA B L E 2 (Continued) specificity of 75-76%.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…11 Although previous studies have evaluated the diagnostic usefulness of blood PCR in patients with invasive aspergillosis or mucormycosis, 4,[12][13][14] there are limited data on the differential diagnosis of invasive aspergillosis and mucormycosis by using blood fungal PCR in patients with suspected invasive mould infections. 15,16 In In our study, blood PCR invasive aspergillosis showed lower sensitivity and higher specificity than in previous studies. TA B L E 2 (Continued) specificity of 75-76%.…”
Section: Discussioncontrasting
confidence: 47%
“…In this context, this study provides important data on the usefulness of fungal PCR for the differential diagnosis of invasive mould infections to the current fungal PCR literature. Shokouhi et al reported that serum PCR was as an unreliable tool for diagnosing immunocompromised patients with suspected fungal sinus infection, showing negative results for all 31 serum samples with sensitivities of 1.3 ng and 12 pg for mucormycosis and aspergillosis, respectively 16 . However, our finding suggests that blood PCR may be useful in a clinical setting in which biopsy is not feasible, or in which morphologic or sparse fungal elements have limited the interpretation of histologic findings.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The clinical manifestation and duration of the illness depend on host’s immune status and vary from innocuous and slight presentation to alive threatening complications [ 6 ]. Because of the growing prevalence of chemotherapy, human immunodeficiency virus (HIV) infections, and diabetes mellitus, the number of susceptible immune-compromised hosts is expanding [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, decreased sensitivity of galactomannan antigen assay is observed in patients with anti-mold therapy [115]. In addition, Aspergillus PCR from blood and BAL fluid is introduced to confirm the diagnosis and identify specific Aspergillus species with certain mutations related to triazole resistance [109,[116][117][118][119][120][121][122][123][124]. Nonetheless, revised EORTC/MSG criteria for diagnosing invasive fungal infections may be applied mainly for neutropenic patients or immunocompromised patients.…”
Section: Diagnosis Of Invasive Aspergillus Infections: Challenge In the Fieldmentioning
confidence: 99%